1993
DOI: 10.1002/j.1460-2075.1993.tb05901.x
|View full text |Cite
|
Sign up to set email alerts
|

A small diffusible signal molecule is responsible for the global control of virulence and exoenzyme production in the plant pathogen Erwinia carotovora.

Abstract: Virulence of the plant pathogen Erwinia carotovora subsp. carotovora is dependent on the production and secretion of a complex arsenal of plant cell wall‐degrading enzymes. Production of these exoenzymes is controlled by a global regulatory mechanism. A virulent mutants in one of the regulatory loci, expI, show a pleiotropic defect in the growth phase‐dependent transcriptional activation of exoenzyme gene expression. The expI gene encodes a 26 kDa polypeptide that is structurally and functionally related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
361
2
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(371 citation statements)
references
References 54 publications
5
361
2
3
Order By: Relevance
“…It was found that the expI gene, which is homologous to the luxI gene of Vibrio fischeri, encodes AI production in E. carotovora. An expI mutant was avirulent when inoculated into tobacco leaves, but virulence was restored by external autoinducer addition (6). To determine the impact of aiiA gene on virulence, the cosmid clone containing the aiiA gene was introduced into E. carotovora strain SCG1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the expI gene, which is homologous to the luxI gene of Vibrio fischeri, encodes AI production in E. carotovora. An expI mutant was avirulent when inoculated into tobacco leaves, but virulence was restored by external autoinducer addition (6). To determine the impact of aiiA gene on virulence, the cosmid clone containing the aiiA gene was introduced into E. carotovora strain SCG1.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, AIs have been identified in several Gram-negative bacteria. AIs are involved in the regulation of a range of biological functions, including Ti plasmid conjugal transfer in Agrobacterium tumefaciens (3), induction of virulence genes in Erwinia carotovora, Erwinia chrysanthemi, Erwinia stewartii, Pseudomonas aeruginosa, Pseudomonas solanacearum, and Xenorhabdus nematophilus (4)(5)(6)(7)(8)(9)(10)(11)(12), regulation of antibiotic production in Pseudomonas aureofaciens and E. carotovora (10,13), regulation of swarming motility in Serratia liquefaciens (14), and biofilm formation in Pseudomonas fluorescens and P. aeruginosa (15,16). Many more bacterial species are known to produce AIs, but the relevant biological functions have not yet been established (17)(18)(19).…”
mentioning
confidence: 99%
“…Response to DF indicates the effect of added DSF on the level of endoglucanase produced by the strains; ¹ indicates less than a twofold increase; þþ indicates at least a 10-fold increase. production of enzymes in other bacteria such as the plant pathogen Erwinia carotovora (Jones et al, 1993;Pirhonen et al, 1993), it was of interest to examine the kinetics of DSF accumulation in relation to enzyme synthesis. Cultures of Xcc strains 8004 containing pIJ3077 (a plasmid with a correctly orientated Tn5lac transcriptional fusion reporter in the prtA protease gene) and 8004 containing pIJ3033 (which is pIJ3020 with a Tn5lac insertion in rpfF ) were inoculated at low density and, at intervals, measurements were made of bacterial growth, ␤-galactosidase and DSF levels.…”
Section: Production Of Dsf In Xcc Culturesmentioning
confidence: 99%
“…The genes aepA and aepH have been described as activators of extracellular enzyme synthesis (Murata et al, 1991;Liu et al, 1993). Other E. carotovora mutants with decreased pectinase production are affected in the expI-expR locus (also called rexI/rexR or carI/carR or hslI ), which is responsible for the cell density control of extracellular enzyme production (Jones et al, 1993;Pirhonen et al, 1993). The ExpI-ExpR couple is homologous to the LuxI-LuxR system of Vibrio fischeri (Meighen, 1991).…”
Section: Introductionmentioning
confidence: 99%